1979
DOI: 10.1073/pnas.76.9.4646
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoproteins in human cerebrospinal fluid.

Abstract: The presence of apolipoproteins A-I, E, C-II, and GIII and the absence of apolipoprotein B was demonstrated in human cerebrospinal fluid. The concentration of apolipoproteins was measured by electroimmunoassay. Apolipoproteins E, C-I1, and C-Il were present in cerebrospinal fluid at 3-5% of their concentration in plasma; the cerebrospinal fluid level of apolipoprotein A-I was 0.4%. Most of the cerebrospinal fluid apolipoproteins were present in the p < 1.21 g/ml i protein fraction. The major apoli proteins of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
194
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(207 citation statements)
references
References 31 publications
13
194
0
Order By: Relevance
“…The diameters of previously identified CSF lipoproteins were 11-13 nm according to Roheim et al (1979) and averaged 13.9 nm according to Pitas et al (1987). In unfractionated CSF we confirmed these observations, demonstrating that the bulk of CSF lipoproteins have sizes (11.6 ±2.2 nm) similar to those of most plasma HDL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diameters of previously identified CSF lipoproteins were 11-13 nm according to Roheim et al (1979) and averaged 13.9 nm according to Pitas et al (1987). In unfractionated CSF we confirmed these observations, demonstrating that the bulk of CSF lipoproteins have sizes (11.6 ±2.2 nm) similar to those of most plasma HDL.…”
Section: Discussionmentioning
confidence: 99%
“…The major CSF apolipoproteins are apoE and apolipoprotein A-I (apoA-I), whereas apolipoprotein B (apoB), which is abundant in blood plasma, is absent from CSF (Roheim et al, 1979). CSF apoE originates in the CNS, whereas plasma apoE is largely produced by the liver (Linton et al, 1991).…”
mentioning
confidence: 99%
“…For CSF fractions (see Fig. 3A and B), the areas of the apoprotein curves were adjusted to reflect the relative apoprotein concentration in total CSF, where apoE -2.9-5.9~.tg/ml (Pitas et al, 1987b;Caisson et al, 1991;Blennow et al, 1994;Lehtimaki et al, 1995), apoAl -4.5 ptg/ml (Roheim et al, 1979;Rifai et al, 1986), apoJ -2.4 g/ml (Choi-Miura et al, 1992), and apoAll -0.5 ,ug/ml (W. Rebeck, personal communication). For astrocyte media fractions (see Fig.…”
Section: Western Analysismentioning
confidence: 99%
“…CSF is produced by the choroid plexus and also contains nonresorbed products derived from the interstitial space of the brain and, to a smaller degree, plasma. Studies have shown that several apolipoproteins are present in the CSF, with the two most abundant being apoE and apoAl (Roheim et al, 1979;Pitas et al, l987b). These proteins appear to reside in distinct lipoprotein particles that are HDLlike in density as determined by gradient centrifugation (Pitas et al, 1987b).…”
mentioning
confidence: 99%
“…In the plasma, apoE is present in a variety of types of lipoproteins such as large very low-density lipoproteins (VLDL) as well as high-density lipoproteins (HDL). In the cerebrospinal fluid (CSF), apoE is only present in lipoproteins that are HDL-like in size (Borghini et al, 1995;LaDu et al, 1998;Pitas et al, 1987b;Roheim et al, 1979). Interestingly, apoE-containing lipoproteins in the CSF are produced predominantly, if not exclusively, by cells within the CNS (Linton et al, 1991).…”
Section: Introductionmentioning
confidence: 99%